Post-illness-onset risk of offending across the full spectrum of psychiatric disorders. Issue 11 (August 2015) - Stevens, H.; Laursen, T. M.; Mortensen, P. B.; Agerbo, E.; Dean, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The link between psychotic disorders and violent offending is well established; knowledge about risk of post-illness-onset offending across the full spectrum of psychiatric disorders is lacking. We aimed to compare rates of any offending and violent offending committed after the onset of illness, according to diagnostic group, with population controls. Method A 25% random sample of the Danish population (n = 521 340) was followed from their 15th birthday until offending occurred. Mental health status was considered as a time-varying exposure in a Poisson regression model used to examine the duration from service contact to the offence. Results Males with any psychiatric contact had an incidence rate ratio (IRR) of 2.91 [95% confidence interval (CI) 2.80–3.02] for any offending; 4.18 (95% CI 3.99–4.38) for violent offending. Associations were stronger for women (IRR 4.17, 95% CI 3.95–4.40 for any offending; 8.02, 95% CI 7.20–8.94 for violent offending). Risk was similar across diagnostic groups for any offending in males, while variation between diagnostic groups was seen for male violent and female offending, both any and violent. Conclusions Risk of offending, particularly violent offending, was elevated across a range of mental disorders following first contact with mental health services. The extent of variation in strength of effect across diagnoses differed by gender.